The culture of child labor as a current expression of neo-colonialism - Conde, Soraya Franzoni (Outlines. Critical Practice Studies, 2024)
This article discusses how the persistence of child labor, especially in Brazil and the United States of America, constitutes a current facet of neo-colonialism. Cultivated as an educational and dignifying activity, exploited child labor persists and is naturalized. Schools, religions, and the legislation contribute to making the working class come to love and naturalize what in the past was understood as torture and punishment, thus jointly acting as a fundamental means of forming a new cultural form: the love of work. Initially, the article discusses how the culture of work is historically founded and then argues against the idealist and postmodern explanations that naturalize it. The argument is based on the understanding that culture has a material basis and is linked to the production and social reproduction of life. Data from the empirical research on child labor in tobacco farming in Brazil and the USA reveal the persistence of the problem among Latino children and families. We conclude with the need to found a new culture for contemporary society, based on other social and economic relations, which allows the working class to free itself from what dominates and exploits it.